Strain Distribution and Drug Susceptibility of Invasive Fungal Infection in Clinical Patients With Systemic Internal Diseases - Zeng, Xuehua; Peng, Mengran; Liu, Guirong; Huang, Yongqing; Zhang, Tingting; Wen, Jing; Lai, Wei; Zheng, Yue (Frontiers in Bioengineering and Biotechnology, 2021)
Background Patients with systemic internal diseases present high risks for invasive fungal infections, which results in increased morbidity and mortality. Identification of high-risk departments and susceptibility systems could help to reduce the infective rate clinically. Correct selection of sensitive anti-fungal drugs not only could improve the cure rate but also could reduce the adverse reactions and complications caused by long-term antifungal drug treatment, which can be especially important in patients with serious systemic diseases. Therefore, the distribution changes of invasive fungal strains in patients with systemic internal diseases and the choice of antifungal drugs in clinical practice should be updated. Objective This work aimed to investigate the incidence, strain distributions, and drug susceptibility of invasive fungal strains isolated from patients with systemic internal diseases. Methods Samples were collected from 9,430 patients who were diagnosed with internal diseases in our hospital from January to December 2018. We then cultured and identified the fungal strains using API 20C AUX. We performed drug sensitivity analysis via the ATB Fungus-3 fungal susceptibility strip. Resistance was defined using the revised Clinical Laboratory Standardization Committee of United States breakpoints/epidemiological cutoff values to assign susceptibility or wild-type status to systemic antifungal agents. Results A total of 179 patients (49 female, 130 male) with fungal infection were included. The high-incidence departments were determined to be the respiratory department (34.64%), intensive care unit (ICU; 21.79%), and hepatology department (9.50%). The susceptible systems for infection were the respiratory tract (sputum, 68.72%, 123/179; secretion retained in the tracheal catheter, 3.35%, 6/179), urinary tract (urine, 9.50%, 17/179), and gastrointestinal tract (feces, 9.50%, 17/179). The major pathogens were Candida (90.50%), Aspergillus (8.93%), and Cryptococcus neoformans (0.56%). The infective candida subgroups were Candida albicans (70.95%), Candida krusei (6.15%), Candida glabrata (5.59%), Candida parapsilosis (3.91%), and Candida tropicalis (3.91%). The susceptibility of non-Aspergillus fungi for amphotericin B was 100.0%. The susceptibility rates of 5-fluorocytocine (5-FC) and voriconazole were 72.73 and 81.82%, respectively, for C. krusei, 98.43 and 100% for C. albicans, and 100% for both drugs for C. glabrata, C. parapsilosis, and C. tropicalis. The susceptibility rates of fluconazole and itraconazole were 0 and 54.55%, respectively, for C. krusei, 20 and 20% for C. glabrata, and 57.14 and 57.14% for C. tropicalis. The resistance rate of C. tropicalis for both fluconazole and itraconazole was 41.43%. Conclusion Patients in the respiratory department, ICU, and hepatology department presented high rates of invasive fungal infections and should include special attention during clinical treatment. The respiratory tract, urinary tract, and gastrointestinal tract were the susceptible systems. Candida, especially C. albicans, was the main pathogen. From the perspective of drug sensitivity, amphotericin B should be given priority in treating the non-Aspergillus fungi infection in patients with systemic internal diseases, while the susceptibility of invasive fungal strains to azoles was variant. These data might provide clinical evidence for the prevention and treatment of invasive fungal infection in patients with systemic internal diseases.